Improvement of adhesion between polyaniline and ion assisted-reaction-treated polypropylene - Lee, CS; Han, S; Beag, YW; Joo, JS; Koh, SK (JOHN WILEY & SONS INC, 2003)
A nonwettable polypropylene (PP) surface was modified by an ion-assisted reaction (IAR) to improve its adhesion with a conjugated polymer, polyaniline (PAN). Hydrogen ions with energies ranging from 0.6 to 1 keV were irradiated on the PP surface in an oxygen gas environment. Ion doses were in the range 5 x 10(14) to 1 x 10(17) ions /cm(2). The lowest static wetting angle of the irradiated PP without blowing oxygen gas was about 60degrees, but that of IAR-treated PP was less than 10degrees; the surface free energy of the modified PP was larger than 64 dyne/cm, and adhesion between PAN and PP passed the Scotch tape test. The main contribution to this improvement was the high concentration of hydrophilic groups on PP. Surface chemistry was investigated by X-ray photoelectron spectroscopy, and hydrophilic functional groups such as C-O, C=O, (C=O)-O were not washed with water. Surface morphology was observed with atomic force microscopy, and surface roughness changed from 8.30 to 20.8 nm after the treatment. (C) 2003 Wiley Periodicals, Inc.